Pengaruh literasi keuangan dan gaya hidup terhadap perilaku konsumtif pengguna aplikasi pinjaman online (peer to peer landing) pada mahasiswa Jawa Timur tahun 2021. - Ramantara, Mahatma (Maliki Interdisciplinary Journal, 2023)
This study aims to investigate the influence of financial literacy and lifestyle on the consumptive behavior of online loan application users in the millennial generation. Financial literacy is measured through knowledge of financial concepts and fund management, while lifestyle involves spending patterns and consumption preferences. The descriptive quantitative method is used to collect data from a sample of millennials who use online loan applications. Regression analysis will be used to assess the relationship between the variables of financial literacy, lifestyle, and consumptive behavior. This research is expected to provide insights into the factors that influence millennials’ consumptive behavior in using online lending apps, as well as implications for the development of financial literacy and consumer education.